Benefits and Challenges of Technology and Information Systems on Performance - Nicholas Renaldo; Suhardjo; Suharti; Suyono; Cecilia (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
In this modern era, technology and information systems are very important in business. explore the relationship between technology, information systems, and organizational performance. The aim of this paper is to provide a better understanding of the role of information technology and systems in improving organizational performance and consider the challenges that may occur. The right methodology for analyzing the topic of technology, information system, and performance is to use a qualitative approach. Information technology and systems have become important components of organizational performance. These systems improve efficiency, communication, decision-making, innovation and more. However, they also present some challenges, including security risks, technical issues, costs and more. The suggestions from this research will be very useful for companies that want to improve performance through the use of technology and information systems.